Encouraging Students To Read The Texts: The Jigsaw Method - Resor, Cynthia (Teaching History: A Journal of Methods, 2008)
"The information in the book will be on the exam" is probably the most common technique used to inspire college history students to read assigned texts. Unfortunately, this vague threat does not always encourage students to read and analyze the assignment carefully. College history students are much more likely to read assigned monographs, chapters, or articles if the instructor provides a specific purpose for the assignment. The jigsaw method is a teaching and learning strategy with a specific purpose that can promote comprehension and retention as well as encourage in-depth scrutiny of assigned readings. Additionally, students enjoy the peer interaction involved in jigsaw activities and instructors appreciate lessons in which students must take the initiative.